Mechanical, thermal properties and morphology of composite coating based on acrylic emulsion polymer and graphene oxide - Hung, Dao Phi; Quan, Vo An; Thanh, Trinh Van; Hiep, Nguyen Anh; Vuong, Nguyen Thien; Phuc, Mac Van (Vietnam Journal of Science and Technology, 2020)
Studied results showed that graphene oxide (GO) had insignificant effect on adhesion of composite coating while graphene oxide improved abrasion resistance of composite coatings. The abrasion durability of studied coatings increased with GO ratio rising to 0.5% and then abrasion resistance of coatings decreased with GO ratio continuous growing up. SEM images witnessed that GO dispersed well into polymer matrix if GO weight ratio was 0.5%. TGA results also illustrated that thermal property of GO composite was better than that of neat coating.